Functional linguistics - Zhongshan da xue (Guangzhou, China). Han Lide yu yan xue wen xian zhong xin (Springer-Verlag, GmbH, 2014)
"Functional Linguistics publishes scholarly articles and reviews in the broad area of functional studies, with a special focus on systemic functional linguistics. The journal aims to provide a platform for the exploration of language and linguistic issues from a functional and meaning-oriented perspective. Areas to be covered in this journal include: language and context, functional grammar, semantic variation, discourse analysis, multimodality, register and genre analysis, educational linguistics, etc."
Keywords: Functionalism (Linguistics) : Periodicals; Systemic grammar : Periodicals; Functionalism (Linguistics); Systemic grammar; Philology & Linguistics